Bachelor-Level Student Dropouts in Nepal: Causes and Strategies for Retention - Bartaula, Anjita (International Research Journal of MMC, 2026)
Student attrition at the undergraduate level represents a critical institutional and socioeconomic challenge within the higher education landscape. This study investigates causes of college dropout, and strategies for their retention. This study adopted a narrative research design in which primary data were gathered from 10 college dropouts in the faculty of education in 2025, whereas secondary data were collected from books, and journal articles. The research findings revealed that undergraduate attrition was driven by an intersection of compounding factors, primarily severe financial constraints, rigid theoretical curricula, lacking practical market relevance, pedagogical disengagement, and a profound deficit in structured institutional support mechanisms like academic advising and career counseling. Psychologically, feelings of academic isolation and low self-esteem further accelerate student alienation. Based on these findings, this study concludes that mitigating student attrition requires a structural shift from reactive management to a holistic, student-centric retention ecosystem. This study is significant because it identifies the major causes of bachelor-level student dropouts in Nepal and provides evidence-based retention strategies to support policymakers, educational institutions, teachers, and other stakeholders in improving student persistence, reducing dropout rates, and enhancing the quality and equity of higher education.